A Review on Increased Incidences, Intensity and Scope of Disasters: Manifestation of Unsustainable Development Practices - Barasa, Beatrice M. O. (Challenging Issues on Environment and Earth Science Vol. 3, 2021)
Over ages, disasters have been considered as natural calamities that humanity has no control or role. However, the frequency, complexity, scope and destructive capacity of disasters continue to escalate over time, implying other factors are at play. A disaster occurs when a hazard interacts with vulnerable settings. Vulnerability refers to the lack the capacity to reduce the probability of the occurrence of disasters or reverting back to normalcy after the disaster. The vulnerabilities of communities are increasing through a myriad of development practices at individual, local, national and international levels. Notable amongst the disaster hazards that have increased over time include: protracted civil strife/wars; emerging diseases; food insecurity; climate change; and pollution. To a large extent, they manifest development practices that do not conform to the tenets of sustainable development as espoused in the Brandtland Commission resolutions, commonly referred to as ‘our common future’. This article reviews selected examples of development practices that have occasioned disasters, debunking the myth that all disasters are entirely attributable to natural causes. The article recommends a raft of practices that should be embraced to ensure development practices are not responsible for the increased incidences, intensity and scope disasters.